Dimensions of reading motivation and their relationships with pleasure reading habits / Hamidah Mohd Ismail - Mohd Ismail, Hamidah (2007)
The creation of habitual readers amongst university students is one of the many goals for academic institutions in Malaysia. However, previous studies have reported an increasing number of reluctant readers amongst Malaysian university students. Empirical studies have shown that when a student's reading motivation is high, reading frequency and interests increase. Motivation to read is one's personal goals, values and beliefs with regard to reading. The present study examines the pleasure reading habits in English amongst a selected group of university students and investigates whether there are any group differences in gender, year of study and family income in the students' dimensions of reading motivation. In addition, the study also investigates the relationships between the students' dimensions of reading motivation and their pleasure reading habits. The theoretical basis of the study corroborated on theories proposed by Wigfield and Guthrie (1997) and Day and Bamford (1998). A heterogeneous sample of one hundred and fifty undergraduate students from a local public university participated in this study. Data obtained for the present study was derived from the main instrument that was a questionnaire; and for triangulation purpose, semi-structured interviews were also conducted. Results from the present study revealed that the selected group of university students was found to read for pleasure in English between one to four books yearly and a majority of the students read for pleasure in English everyday. Gender differences were found to be significant in the dimension of Curiosity, while there were no significant differences on the year of study on any of the ten dimensions. A statistically significant main effect of family income level was found in the dimension of Involvement with the most significant difference shown by students with a monthly family income of less than RM2000. Findings from the present study also revealed that the students' dimension of Expectancy had a moderate relationship with their pleasure reading habits. This study substantiated previous research that reports the multi-dimensional state of reading motivation and most of the stronger dimensions that emerged from the findings were from the domain of intrinsic motivation. Implications for practice included the need for academicians to acknowledge the differences in students' level of reading motivation in order to nurture their pleasure reading habits in English. In addition, academicians could promote intrinsically motivating activities to increase students' self-confidence as good readers. Finally, academicians, university administrators and librarians should work together in creating a "book-rich" environment that would benefit all students.